The Experience of Working With Individuals Who Sexually Offend. (September 2022) - Jeglic, Elizabeth L.; Zulueta, Ines; Katsman, Kseniya
Providing treatment to those who have committed sexual offenses can be difficult and challenging work. Older studies have suggested that service providers may experience changes in mood, symptoms of trauma, and countertransference reactions due to their work. Recent research has found that effective coping and self-care strategies may mitigate these negative outcomes. Given the relative dearth of recent empirical studies, we assessed the prevalence of self-reported mood, trauma symptoms, and countertransference reactions and their relation to coping styles and self-care practices in a sample of 32 male and 52 female therapists who provided treatment to individuals convicted of sexual offenses. As expected, we found minimal levels of clinically significant depressive (4%) and trauma symptoms (9%). Some countertransference reactions to clients were reported, including intense anger, retributive fantasies, sexual attraction, and arousal. A problem-solving coping style was associated with higher levels of psychological well-being, while avoidant coping was related to increased depressive and trauma symptoms. Approximately 10% of therapists with an abuse history reported re-experiencing their own victimization. The majority of therapists reported engaging in self-care practices. The findings are discussed as they pertain to those who provide services to individuals convicted of sexual offenses.